2019
DOI: 10.1038/s41467-018-08058-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the circuit for blindsight to reveal the critical role of pulvinar and superior colliculus

Abstract: In patients with damage to the primary visual cortex (V1), residual vision can guide goal-directed movements to targets in the blind field without awareness. This phenomenon has been termed blindsight, and its neural mechanisms are controversial. There should be visual pathways to the higher visual cortices bypassing V1, however some literature propose that the signal is mediated by the superior colliculus (SC) and pulvinar, while others claim the dorsal lateral geniculate nucleus (dLGN) transmits the signal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 53 publications
4
88
1
Order By: Relevance
“…These findings suggest that the SC and pulvinar constitute the subcortical visual pathway for innate face detection. Neuroanatomical, non-invasive imaging and neurophysiological studies reported existence of this subcortical pathway consisting of the SC, pulvinar, and amygdala in animals and humans (Linke et al, 1999;Day-Brown et al, 2010;Tamietto et al, 2012;Garvert et al, 2014;Rafal et al, 2015;Elorette et al, 2018;Kinoshita et al, 2019). These findings suggest that the SC is a first node in the subcortical pathway, where retinal inputs are integrated into facial information.…”
Section: Resultsmentioning
confidence: 84%
“…These findings suggest that the SC and pulvinar constitute the subcortical visual pathway for innate face detection. Neuroanatomical, non-invasive imaging and neurophysiological studies reported existence of this subcortical pathway consisting of the SC, pulvinar, and amygdala in animals and humans (Linke et al, 1999;Day-Brown et al, 2010;Tamietto et al, 2012;Garvert et al, 2014;Rafal et al, 2015;Elorette et al, 2018;Kinoshita et al, 2019). These findings suggest that the SC is a first node in the subcortical pathway, where retinal inputs are integrated into facial information.…”
Section: Resultsmentioning
confidence: 84%
“…The ventral stream extends to the temporal cortex, and contains a group of neurons responding to a specific category of visual objects (36,37). Visual information mediated via the SC projects to the higher visual cortices of the dorsal stream (11)(12)(13)(14). The excellent perception of moving grating direction in the impaired right visual field (Figure 3D) may be explained as a function of this projection.…”
Section: Discussionmentioning
confidence: 98%
“…When the V1 is damaged, the visual fields opposite to the damaged V1 are impaired, a condition known as cortical blindness (3)(4)(5). However, patients with cortical blindness have unconscious visual functions called blindsight (6,7), possibly through visual information obtained from the superior colliculus (SC), which in turn projects to the amygdala (8)(9)(10) and the higher visual cortex (11)(12)(13)(14). Fresh cortical blindness sometimes spontaneously recovers (15), and the recovery is facilitated by early rehabilitation (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In rabbits, however, the inactivation of SC led to a strong attenuation of responses in lateral posterior nucleus (which is a part of the LP-pulvinar complex in non-primate species: mice, rats, rabbits, cats, and tree shrews) (Casanova and Molotchnikoff, 1990). Furthermore, selective microstimulation of the superficial layers of the SC in macaques has been shown to elicit (monosynaptic) responses in the ventral pulvinar (Kinoshita et al, 2019), in agreement with earlier work that identified the projection from SC to area MT via ventral pulvinar (Berman and Wurtz, 2011).…”
Section: Possible Sources Of Eye Position Signals In Dorsal Pulvinarmentioning
confidence: 99%
“…Extrapolating from these ventral pulvinar studies to the dorsal pulvinar, the potential influence of SC inputs to dPul (Wurtz et al, 2005) might be outweighed by more extensive cortical driving inputs (Rovó et al, 2012;Bickford, 2016). To fully elucidate complex cortico-pulvinar-cortical loops and subcortical inputs to pulvinar, it would be crucial to manipulate the specific projections from and to the pulvinar, using pathway-selective techniques, such as optogenetics and/or viral vectors (Schmitt et al, 2017;Kinoshita et al, 2019).…”
Section: Possible Sources Of Eye Position Signals In Dorsal Pulvinarmentioning
confidence: 99%